2011
DOI: 10.4236/jep.2011.21007
|View full text |Cite
|
Sign up to set email alerts
|

Higher Temperatures Were Closely Associated with Higher Ambulance Transports in Takamatsu Area, Japan

Abstract: The link between high temperatures and ambulance transports in Takamatsu area, Japan was investigated. Monthly observations for ambulance transports (2004-2008) were obtained from Fire Department Service in Takamatsu. Data of temperatures in Takamatsu area, Japan (2004-2008) were used by Japan Meteorological Agency. Effect of high temperatures on ambulance transports was analyzed. By using data from July to September, there were not clear differences of mean temperatures and ambulance transports among years. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…We have previously reported that higher air temperature was closely associated with higher ambulance transports due to heat stroke by ecological study [1,2]. In Takamatsu area, located on the northern shore of Shikoku Island, Japan, changes in mean air temperature were estimated 1.8°C for 50 years [3], and higher air temperature was closely linked to higher total ambulance transports by using monthly data [4]. Taken together, higher air temperature and its related health problems have become public health challenge in Takamatsu area as well as all over Japan.…”
Section: Introductionmentioning
confidence: 93%
“…We have previously reported that higher air temperature was closely associated with higher ambulance transports due to heat stroke by ecological study [1,2]. In Takamatsu area, located on the northern shore of Shikoku Island, Japan, changes in mean air temperature were estimated 1.8°C for 50 years [3], and higher air temperature was closely linked to higher total ambulance transports by using monthly data [4]. Taken together, higher air temperature and its related health problems have become public health challenge in Takamatsu area as well as all over Japan.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, it is expected the climatic changes associated with global warming will have a serious impact on human beings [4,5]. We have also previously reported that higher air temperatures were associated with the total number of ambulance transports in Takamatsu city [6] and Okayama city [7], Japan. However, the relation between high air temperatures and ambulance transports stratified by heat stroke still remains to be investigated in Japan.…”
Section: Introductionmentioning
confidence: 97%
“…Piver et al showed that heat stroke was associated with prolonged exposures to higher air temperatures that usually occur in the summer months of July and August in 1980-1995 in Tokyo [13]. In our previous study, higher air temperature was closely associated with higher ambulance transports in Takamatsu and Okayama city using monthly data [3,4]. We also found that high air temperature was associated with ambulance transports by using daily data in Osaka area, Japan in this study.…”
Section: Discussionmentioning
confidence: 55%
“…We have previously showed that estimated changes in mean temperature was 1.6˚C for 50 years in Osaka areas, Japan [2]. In addition, by using monthly data, higher air temperature was associated with ambulance transports in Takamatsu [3] and Okayama [4] areas, Japan. Basu et al also reported that the relation between elevated ambient air temperature and mortality in their review [5].…”
Section: Introductionmentioning
confidence: 99%